Increasing Endocannabinoid Tone Alters Anxiety-Like and Stress Coping Behaviour in Female Rats Prenatally Exposed to Valproic Acid - Thornton, Aoife M. (Molecules, 2021)
Given the sex differences evident in the prevalence of autism, there is an increased awareness of the importance of including females in autism research to determine sexual dimorphism and sex-specific treatments. Cannabinoids and endocannabinoid modulators have been proposed as potential novel treatments for autism-related symptoms; however, few studies to date have examined if these pharmacological agents elicit sex-specific effects. The aim of the present study was to use the valproic acid (VPA) model of autism to compare the behavioural responses of male and female rats and examine the effects of increasing endocannabinoid tone on the behavioural responses of VPA-exposed female rats. These data revealed that VPA-exposed male, but not female, rats exhibit reduced social responding in the three-chamber and olfactory habituation/dishabituation (OHD) test during adolescence. In comparison, VPA-exposed female, but not male, adolescent rats exhibited anxiety-like behaviour in the elevated plus maze (EPM) and open field test (OFT). In VPA-exposed female rats, increasing 2-AG levels augmented anxiety-like behaviour in the EPM and OFT, while increasing AEA levels reduced stress coping behaviour in the swim stress test. These data highlight sexual dimorphic behaviours in the VPA model and indicate that enhancing endocannabinoid levels may exacerbate negative affective behaviour in VPA-exposed females. Thus, considerations should be paid to the possible sex-specific effects of cannabinoids for the treatment of symptoms associated with autism.